Women's Boards, Women's Ownership, And The Growth Of Indonesian Rural Banks - Muhammad Umar Mai; Kristianingsih; Sudrajat; Iwan Setiawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
This study examines the impact of women’s representation in corporate governance—specifically women on the board of commissioners, female board chairs, and women’s ownership—on the growth of rural banks (BPR) in West Java, Indonesia. Using an unbalanced panel dataset of 235 BPRs over the period 2015–2023 (1,968 bank-year observations), this study employs a two-step System Generalized Method of Moments (2SYS-GMM) to address potential endogeneity issues. The results show that female board chairs and women’s ownership have a significant positive effect on BPR asset growth, while the presence of women as board members does not exhibit a significant impact. These findings highlight the differentiated roles of women in governance structures and suggest that leadership position and ownership involvement matter more than mere representation. This study contributes to the corporate governance literature by providing new empirical evidence on the role of women’s ownership and leadership in fostering bank growth in the context of Indonesian rural banks.